Terminology of inform ation consulting in the theory and practice of library science - Zbanatska Alona (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is in the analysis of the main terms related to the information consulting in librarianship theory and practice, through the prism of scientific views on consulting. Research methods are general scientific methods of cognition, specifically analysis and synthesis, generalization, interpretation. In particular, terminological analysis helped clarify the essence of concepts related to information consulting in librarianship. Scientific novelty. The main concepts related to information consulting in librarianship have been identified and analyzed. Conclusions. During the implementation of information consulting in the library sphere, a conceptual apparatus related to the internal and external activities of library institutions is formed. The analysis of the existing apparatus made it possible to reveal the content of the main key concepts, such as "information consulting", "library consulting", "information consultation", "library consultation", which are actively used in librarianship. However, the concepts of "library consultation" and "information consultation" are not adapted to use in modern Ukrainian librarianship, and therefore are replaced or equated with other concepts. In our opinion, in the context of the formation of the conceptual apparatus of information consulting indomestic librarianship, it is appropriate to introduce the term "library consultant" into scientific circulation. Modern librarian terminology continues to be formed under the influence of information and communication technologies and replenished by borrowings from related fields of knowledge and terms of foreign origin, and this creates a systematic basis for the deployment of further scientific research.